2014
DOI: 10.1016/j.bone.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone Pb accumulation: Cause and effect of altered bone turnover

Abstract: This paper assesses the magnitude of Pb uptake in cortical and trabecular bones in healthy animals and animals with altered balance in bone turnover, and the impact of exposure to Pb on serum markers of bone formation and resorption. The results reported herein provide physiological evidence that Pb distributes differently in central compartments in Pb metabolism, such as cortical and trabecular bone, in healthy animals and animals with altered balance in bone turnover, and that exposure to Pb does have an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The body burden of cadmium was assessed as being approximately two-fold higher in smokers than in non-smokers [18] , [7] , [19] . The impact of smoking on the lead body burden is observed through a sequestration in bones [20] , [21] , [22] , but not in blood [23] , [24] , while no effect from smoking could be observed in the case of arsenic [25] , or mercury [26] , [27] . Surveys also showed that smoking is not an important source for nickel [28] .…”
Section: Introductionmentioning
confidence: 95%
“…The body burden of cadmium was assessed as being approximately two-fold higher in smokers than in non-smokers [18] , [7] , [19] . The impact of smoking on the lead body burden is observed through a sequestration in bones [20] , [21] , [22] , but not in blood [23] , [24] , while no effect from smoking could be observed in the case of arsenic [25] , or mercury [26] , [27] . Surveys also showed that smoking is not an important source for nickel [28] .…”
Section: Introductionmentioning
confidence: 95%
“…Most biochemical markers of bone resorption are related to collagen breakdown products or to various collagen crosslinks and telopeptides [1113]. At present, serum C-terminal peptide-bound crosslinks of type I collagen (CTX-1) have been chosen as the reference standard for bone resorption rate, whereas osteocalcin is considered a good marker of bone formation [1416]. Also, osteocalcin is a bone-specific protein that acts as a hormone regulating glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Bone accumulates lead throughout most of the human life span but, at the same time, lead is mobilised from bone by remodelling. In adults, approximately 90 % of the total body burden of lead found in bones (Brito et al, 2014). However, in children, only 70 % of the body burden is found…”
Section: Accumulationmentioning
confidence: 99%